The Lean Enterprise at the Design Office - Elmosalmi, Dawlat; Ibrahim, Mohamed Mohsen (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
This paper presents the lean practice implementation, which led to a transformation in the design offices/projects explaining how implementing lean principles is affecting the projects at the design phase and also affecting the whole system at the design firm. The paper is divided into two parts; theoretical and practical. The theoretical part will explain lean concept definition, values and wastes, wastes solutions, lean principles and levels of lean implementation. The practical part will present a case study for a successful lean transformation in a consultancy firm showing the challenges faced and the steps for a successful implementation on office activities and on projects as well based on a company’s experience and observations reducing wastes and adding value to the work process within the organization to achieve the three parts goal of better, cheaper and faster projects. This research will be enriched by the audiences’ interaction, sharing different experiences in lean transformation for maximum benefits.